Restoring CFTR function with Orkambi decreases the severity of alcohol-induced acute pancreatitis - Venglovecz Viktória; Grassalkovich Anna; Tóth Emese; Ébert Attila; Gál Eleonóra; Korsós Marietta Margaréta; Maléth József; Rakonczay Zoltán; Galla Zsolt; Monostori Péter; Hegyi Péter (2024)
Heavy alcohol intake is one of the most common causes of acute pancreatitis (AP). We have previously shown that ethanol (EtOH) decreases the expression and activity of the cystic fibrosis transmembrane conductance regulator (CFTR), which plays a key role in alcohol-induced AP development. The prescription drug, Orkambi (a combination of ivacaftor and lumacaftor) can correct impaired CFTR function and expression in cystic fibrosis (CF) patients. Thus, the present study aimed to investigate whether Orkambi can mitigate alcohol-induced AP. Intact guinea-pig pancreatic ducts were pre-treated with different concentrations of ethanol (EtOH; 30, 50 and 100 mm) for 12 h alone or in combination with ivacaftor (VX770) and/or lumacaftor (VX-809), and CFTR expression and activity were evaluated by immunostaining and by the patch clamp technique, respectively. Alcoholic AP was induced in Orkambi-treated guinea-pigs, and standard laboratory and histological parameters were measured. Ivacaftor and lumacaftor alone or in combination dose-dependently restored the apical expression and activity of CFTR after EtOH treatment in vitro. Oral administration of Orkambi reduced the severity of alcohol-induced AP and restored impaired CFTR activity and expression. Orkambi is able to restore the CFTR defect caused by EtOH and decreases the severity of alcohol-induced pancreatitis. This is the first in vivo pre-clinical evidence of Orkambi efficacy in the treatment of alcohol-induced AP. KEY POINTS: Acute pancreatitis is one of the leading causes of hospital admission among gastrointestinal diseases in which the lack of a specific drug therapy plays a crucial role. The cystic fibrosis transmembrane conductance regulator (CFTR) plays an essential role in pancreatic ductal HCO3- secretion; inappropriate CFTR function, as seen in heavy alcohol consumption, increases the risk of pancreatitis development. CFTR modulators are able to prevent the inhibitory effect of ethanol and reduce pancreatic ductal injury and the severity of alcohol-induced pancreatitis. CFTR modulators present a novel option in the pharmacotherapy of alcohol-induced pancreatitis by enhancing pancreatic functions or preventing recurrence.
Keywords: Általános orvostudomány